Perbedaan Perkembangan Bayi Usia 3 – 6 Bulan yang Diberi Dan tidak Diberi ASI Eksklusif di Kecamatan Purworejo Kabupaten Purworejo Jawa Tengah - Desti Tiara Putri A. (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Exclusive breastfeeding is breastfeeding infants 0 until 6 months old with no other supplementary feeding. Breastfeeding has advantages which include of three aspects, namely nutrition, immunity aspects and psychological aspects form the fabric of affection are important for mental development and intelligece. The purpose of this study to determine and analyze the differences in the development of infants aged 3 until 6 months were given and not exclusively breast-fed at the Work Area Health Center District of Purworejo. This type of research is a quantitative approach to analytical survey with cross sectional design. Sampling techniques in this research using proporsional random sampling. The Population of 278 infants. Subjects of this study for cases and controls, respectively 45 babies. Based on these results the development of babies aged 3 until 6 months were given and not exclusively breast-fed values obtained ρ = 0.001 , ρ < 0.05 , so it can be said that there is a significant difference between the development of infants aged 3-6 months were given and no exclusively breast-fed at the Work Area Health Center District of Purworejo . There are differences in the development of infants aged 3 until 6 months were given and not exclusively breast-fed at 3 Purworejo with District Health Clinics. Babies who get exclusively breast-fed more likely to have normal development than those who not exclusively breast-fed. While, confounding variables consisting of the economy, child gender, maternal age, maternal parity and maternal education did not prove to be a meaningful relationship, initially as a confounding variable that was not prove.